Analisis Pengaruh Inflasi, PDRB, dan Upah Minimum terhadap Penyerapan Tenaga Kerja di Jawa Timur - Warapsari, Esthi Bhakti; Hidayat, Wahyu; Boedirochminarni, Arfida (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2021)
The population growth in Indonesia has been increasing steadily, so has the population growth in East Java Province. An increase in population will lead to an increase in the number of workers. The increasing number of workers will become a problem in the world of employment, if the number of workers available is not proportional to the demand for workers who are able to absorb. The results of this study indicate that the results of the study were negative and insignificant to the workforce in East Java Province with a coefficient of -0,000508 and a probability yield of 0.3650, while the GRDP had a positive and significant effect on labor in the East Java Province with a coefficient of 0,026689 and the probability result of 0.0468, and the minimum wage have a positive and significant effect on labor in the Province of East Java with a coefficient result of 0.132291 and a probability result of 0.0000.